1996
DOI: 10.1021/bi960022r
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Bovine Angiogenin by 1H Nuclear Magnetic Resonance Spectroscopy,

Abstract: The three-dimensional structure of bovine angiogenin has been determined using two- and three-dimensional proton NMR spectroscopy. The solution structure is very close to that recently determined by X-ray diffraction analysis. This structure appears well defined, even if five loops and one helix exhibit greater flexibility. Analysis of the active site geometry confirms the position of the Glu-118 residue which obstructs the pyrimidine binding site. There is no experimental evidence of an unobstructed conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…1), as compared with the homologous region of RNase-1 and -2, became clear. Nuclear magnetic resonance (NMR) studies on the structure showed that the general structure provided by X-ray crystallography also is valid in solution, including the occluded pyrimidine-binding-site cleft [76]. In addition, the orientation of the imidazole rings of both active-site histidines is unambiguously the same as in RNase-1, supporting the idea of conserved catalytic properties between these enzymes.…”
Section: Multi-author Review Articlementioning
confidence: 74%
“…1), as compared with the homologous region of RNase-1 and -2, became clear. Nuclear magnetic resonance (NMR) studies on the structure showed that the general structure provided by X-ray crystallography also is valid in solution, including the occluded pyrimidine-binding-site cleft [76]. In addition, the orientation of the imidazole rings of both active-site histidines is unambiguously the same as in RNase-1, supporting the idea of conserved catalytic properties between these enzymes.…”
Section: Multi-author Review Articlementioning
confidence: 74%
“…It is also suggested that substrate binding will be facilitated only after some conformational changes are effected. 4 Such conformational changes have not been observed in the nmr solution structure of bovine angiogenin 8 and structures of ligand-bound angiogenin are not available as yet. Another important loop in angiogenin is the one connecting strands 4 and 5 (residues 85-92 in HAng and 86 -93 in BAng).…”
Section: Introductionmentioning
confidence: 99%
“…Though angiogenin's primary biological role is that of stimulating the growth of blood vessels,2 the RNase activity nevertheless seems to be an important function of the protein 3. Structural information on angiogenin has so far been confined to only the native form and its mutants 4–8…”
Section: Introductionmentioning
confidence: 99%